2013
DOI: 10.1007/s10577-013-9381-9
|View full text |Cite
|
Sign up to set email alerts
|

Emerin and histone deacetylase 3 (HDAC3) cooperatively regulate expression and nuclear positions of MyoD, Myf5, and Pax7 genes during myogenesis

Abstract: The spatial organization of chromatin is critical in establishing cell-type dependent gene expression programs. The inner nuclear membrane protein emerin has been implicated in regulating global chromatin architecture. We show emerin associates with genomic loci of muscle differentiation promoting factors in murine myogenic progenitors, including Myf5 and MyoD. Prior to their transcriptional activation Myf5 and MyoD loci localized to the nuclear lamina in proliferating progenitors and moved to the nucleoplasm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
96
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(108 citation statements)
references
References 46 publications
11
96
0
Order By: Relevance
“…As HDAC3 has been shown to bind the nuclear envelope protein emerin in muscle progenitors (Demmerle et al, 2013) and HDAC1‐3 have been shown to bind emerin and BAF in neuroblastoma cells (Tsai et al, 2015), we cannot rule out the possibility that tissue‐specific interactions of nuclear envelope proteins with diverse epigenetic enzymes might occur (Batrakou, Las Heras, Czapiewski, Mouras, & Schirmer, 2015; Worman & Schirmer, 2015). Along this line, mutations causing EDMD2 do not impair lamin A/C‐HDAC2 interaction (this study), while defects in emerin‐HDAC3 binding have been reported in EDMD1 (Collins, Ellis, & Holaska, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As HDAC3 has been shown to bind the nuclear envelope protein emerin in muscle progenitors (Demmerle et al, 2013) and HDAC1‐3 have been shown to bind emerin and BAF in neuroblastoma cells (Tsai et al, 2015), we cannot rule out the possibility that tissue‐specific interactions of nuclear envelope proteins with diverse epigenetic enzymes might occur (Batrakou, Las Heras, Czapiewski, Mouras, & Schirmer, 2015; Worman & Schirmer, 2015). Along this line, mutations causing EDMD2 do not impair lamin A/C‐HDAC2 interaction (this study), while defects in emerin‐HDAC3 binding have been reported in EDMD1 (Collins, Ellis, & Holaska, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, HDAC2 has been shown to suppress p21 expression in human hepatocellular carcinoma via its binding to an Sp1‐binding site (Noh et al, 2011). On the other hand, it has been demonstrated that lamin A/C establishes direct interactions with histone deacetylases including SIRT1 (Cenni et al, 2014; Liu et al, 2012), SIRT6 (Ghosh, Liu, Wang, Hao, & Zhou, 2015), and HDAC1 (Kubben et al, 2016), while lamin partners at the nuclear envelope such as emerin, BAF, and LAP2beta interact with HDAC3 (Demmerle, Koch, & Holaska, 2013) or HDAC2 (Tsai et al, 2015). Moreover, lamin A/C has been demonstrated to bind gene promoters or neighboring domains and this binding has been linked to distinct transcriptional outcomes (Lee, Welton, Smith, & Kennedy, 2009; Lund & Collas, 2013; Mattout et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Depletion of repressive chromatin modifications enriched in LADs such as H3K9me2/3 results in disrupted lamina association (Zullo et al 2012;Bian et al 2013;Demmerle et al 2013;Kind et al 2013;Harr et al 2015), suggesting that the marks not only provide for silencing but also themselves contribute to locus affinity for the periphery. At the same time, specific nuclear envelope proteins are important for peripheral tethering of endogenous developmentally repositioning loci (Zullo et al 2012;Solovei et al 2013;Robson et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…(BAF) (23,30). Emerin also interacts with HDAC3 to regulate the HDAC3 localization and activity at the nuclear periphery (24,31).…”
Section: Significancementioning
confidence: 99%